( 1 ) x 0 2 a 2 + y 0 2 b 2 + z 0 2 c 2 = 1 {\displaystyle (1){\frac {x_{0}^{2}}{a^{2}}}+{\frac {y_{0}^{2}}{b^{2}}}+{\frac {z_{0}^{2}}{c^{2}}}=1} ( 2 ) z − z 0 = − c x o ( x − x o ) a 2 1 − x 0 2 a 2 − y 0 2 b 2 − c y o ( y − y o ) b 2 1 − x 0 2 a 2 − y 0 2 b 2 {\displaystyle (2)z-z_{0}=-{\frac {cx_{o}(x-x_{o})}{a^{2}{\sqrt {1-{\frac {x_{0}^{2}}{a^{2}}}-{\frac {y_{0}^{2}}{b^{2}}}}}}}-{\frac {cy_{o}(y-y_{o})}{b^{2}{\sqrt {1-{\frac {x_{0}^{2}}{a^{2}}}-{\frac {y_{0}^{2}}{b^{2}}}}}}}}
Ось так:
S 1 = ( − C 2 − C 4 , C 2 , C 2 − C 4 , C 4 ) {\displaystyle S_{1}=(-C_{2}-C_{4},C_{2},C_{2}-C_{4},C_{4})\,} S 2 = ( C 1 , C 2 , C 3 , − C 1 − C 3 ) {\displaystyle S_{2}=(C_{1},C_{2},C_{3},-C_{1}-C_{3})\,} S 3 = ( − C 3 − C 4 , C 2 , C 3 , C 4 ) {\displaystyle S_{3}=(-C_{3}-C_{4},C_{2},C_{3},C_{4})\,}
b 1 ∈ d i m S 3 / S 2 = ? {\displaystyle b_{1}\in dimS_{3}/S_{2}=?\,}